Effect of extrusion process on antioxidant and ACE inhibition properties from bovine haemoglobin concentrate hydrolysates incorporated into expanded maize products - Cian, Raúl Esteban (2011)
Extrusion process has been widely used for the development of many functional foods. The aim of this study was to assess the effect of extrusion process on antioxidant and ACE inhibition properties from bovine hemoglobin concentrate (BHC) hydrolysates (P, FC, PF and FCF). Extrusion was carried out with a Brabender single screw extruder. The ACE inhibition and the antioxidant capacity (AC) were estimated by the inhibition of the angiotensin-converting enzyme and the inhibition of ABTS+ radical cation expressed as Trolox equivalent antioxidant capacity (TEAC), respectively. The ACE inhibition and TEAC values from hydrolysates were significantly higher than that from BHC. The highest ACE inhibition corresponded to P hydrolysate and the highest TEAC corresponded to PF and FCF hydrolysates. The ACE inhibition  and AC from extruded products with added hydrolysates were higher than that from maize control, however the extrusion process modified both, ACE inhibition  and of AC formerly present in hydrolysates.